Grid Connection and Transmission Scheme of Large-Scale Offshore Wind Power - Zhang Zhankui; Shi Wenhui; Qu Jixian; Bai Hong (中国工程科学, 2021)
Offshore wind power is an important direction of global wind power development. Economical and efficient grid connection of large-scale offshore wind power is a core challenge faced by offshore wind power construction in China. This article first summarizes the development status of offshore wind power in China and abroad and the global development trends. Subsequently, it elaborates the technical characteristics and representative applications of two typical scenarios: grid connection of single offshore wind farms and transmission of large-scale offshore wind power clusters. After analyzing the challenges faced by the grid connection and transmission of offshore wind power in China, we propose an overall development strategy and conduct adaptability analysis on the grid connection and transmission schemes under the aforementioned scenarios. To build first-class offshore wind power grid connection and transmission projects that adapt to China’s national conditions and to promote energy transformation, we propose that China should conduct unified planning after verifying its national resource reserves of offshore wind power; strengthen independent innovation to break through the key technologies; improve the supporting mechanism to ensure high quality development of offshore wind power; and promote international industrial cooperation.